Nods of Agreement: Webcam-Driven Avatars Improve Meeting Outcomes and Avatar Satisfaction Over Audio-Driven or Static Avatars in All-Avatar Work Videoconferencing - Ma, Fang; Zhang, Ju; Tankelevitch, Lev; Panda, Payod; Asadi, Torang; Hewitt, Charlie; Petikam, Lohit; Gillies, Marco; Pan, Xenui; Rintel, Sean; Wilczkowiak (SHE/HER), Marta (CSCW 2025, 2025)
Avatars are edging into mainstream videoconferencing, but evaluation of how avatar animation modalities contribute to work meeting outcomes has been limited. We report a within-group videoconferencing experiment in which 68 employees of a global technology company, in 16 groups, used the same stylized avatars in three modalities (static picture, audio-animation, and webcam-animation) to complete collaborative decision-making tasks. Quantitatively, for meeting outcomes, webcam-animated avatars improved meeting effectiveness over the picture modality and were also reported to be more comfortable and inclusive than both other modalities. In terms of avatar satisfaction, there was a similar preference for webcam animation as compared to both other modalities. Our qualitative analysis shows participants expressing a preference for the holistic motion of webcam animation, and that meaningful movement outweighs realism for meeting outcomes, as evidenced through a systematic overview of ten thematic factors. We discuss implications for research and commercial deployment and conclude that webcam-animated avatars are a plausible alternative to video in work meetings. KEYWORDS: videoconferencing, work, avatar animation modalities, satisfaction, outcomes, effectiveness, alignment, comfort, inclusivity, expression, perception, preference